2023
DOI: 10.1007/s00262-022-03359-2
|View full text |Cite|
|
Sign up to set email alerts
|

Real-world multicentre cohort of first-line pembrolizumab alone or in combination with platinum-based chemotherapy in non-small cell lung cancer PD-L1 ≥ 50%

Abstract: Introduction Pembrolizumab alone (IO-mono) or in combination with platinum-based chemotherapy (CT-IO) is first-line standard of care for advanced non-small cell lung cancer (NSCLC) patients with PD-L1 ≥ 50%. This retrospective multicentre study assessed real-world use and efficacy of both strategies. Methods Patients with advanced NSCLC PD-L1 ≥ 50% from eight hospitals who had received at least one cycle of IO-mono or CT-IO were included. Overall survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Several analyses of real-world data obtained from lessselected aNSCLCs [3][4][5][6][7] confirmed the findings of the Keynote 024 trial. A French nationwide study evaluated the efficacy of pembrolizumab monotherapy given to 845 patients, 20% with brain metastases at diagnosis and > 20% with ECOG PS = 2.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Several analyses of real-world data obtained from lessselected aNSCLCs [3][4][5][6][7] confirmed the findings of the Keynote 024 trial. A French nationwide study evaluated the efficacy of pembrolizumab monotherapy given to 845 patients, 20% with brain metastases at diagnosis and > 20% with ECOG PS = 2.…”
supporting
confidence: 54%
“…According to the findings of those 2 studies, ECOG PS ≥2 was an independent factor associated with poorer OS 3,4 . That observation was echoed in other reports 5–12 . The results of a prospective, observational study on 40 patients with ECOG PS = 2 or ≥75 years old, with ≥1% PD-L1 expression on their aNSCLC cells showed that median (95% CI) OS on first-line pembrolizumab lasted 11.6 (1.4–NR) months for patients with ECOG PS = 2 and 11.6 (7.4–18.1) months for the elderly 9 .…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…which included patients who received 1L IO, survived at least 6 months and had an ECOG PS of 0-1 showed a median OS of 19.6 months ( 16 ). Another retrospective study showed the survival was better for the NSCLC patients who were alive at 12 weeks after starting single agent pembrolizumab compared to the whole cohort; however, the median OS was not reached when the data was published ( 17 ). The frequency of death at 12 weeks was 11% for those who received single agent pembrolizumab and 15.2% for the pembrolizumab and chemotherapy combination group ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study showed the survival was better for the NSCLC patients who were alive at 12 weeks after starting single agent pembrolizumab compared to the whole cohort; however, the median OS was not reached when the data was published ( 17 ). The frequency of death at 12 weeks was 11% for those who received single agent pembrolizumab and 15.2% for the pembrolizumab and chemotherapy combination group ( 17 ). In our study, 21% of the patients died within 3 months of starting IO.…”
Section: Discussionmentioning
confidence: 99%